Thyme Oil Reduces Biofilm Formation and Impairs Virulence of Xanthomonas oryzae - Singh, Akanksha; Gupta, Rupali; Tandon, Sudeep; Pandey, Rakesh (Frontiers in Microbiology, 2017)
Xanthomonas oryzae pv. oryzae (Xoo), a common bacterial plant pathogen regulates its virulence and biofilm formation attribute via a chemical method of communication. Disabling this mechanism offers a promising alternative to reduce the virulence and pathogencity of the microorganism. In this study, the effect of thyme (THY) oil on Quorum Sensing (QS) mediated synthesis of various virulence factors and biofilm formation was analyzed. Treatment of Xoo with 500 ppm THY oil displayed a significant diminution in swimming, swarming, exopolysaccharide and xanthomonadin secretion. However, no effect was observed on bacterial growth kinetics and metabolic activity of the cells. Results were further authenticated by RT-qPCR as significant reduction in motA, motB and flgE genes was observed upon THY oil treatment. Similarly, the expression of some extracellular enzyme genes such as endoglucanase, xylanase, cellobiosidase and polygalacturonase was also found to be significantly reduced. However, biochemical plate assays revealed insignificant effect of 500ppm THY oil on secretion of protease, cellulase and lipase enzymes. The rpfF gene known to play a crucial role in the virulence of the phytopathogenic bacteria was also significantly reduced in the THY oil treated Xoo cells. HPTLC analysis further revealed significant reduction in DSF and BDSF signalling molecules when Xoo cells were treated with 500 ppm THY oil. Disease reduction was observed in in-vitro agar plate assay as lesion length was reduced in THY oil treated Xoo cells when compared with the alone treatment. GC-MS result revealed thymol as the active and major component of THY oil which showed potential binding with rpfF gene. Application of 75 µM thymol resulted in downregulation of gumC, motA, estA, virulence acvB and pglA along with rpfF. The other genes such as cheD, flgA, cheY, and pilA, were not found to be significantly affected. Overall, the results clearly indicated THY oil and its active component Thymol to be a potential candidate for the development of anti-virulence agent which in future when applied in combination with conventional bactericides might not only help in lowering the dose of bactericides but also be successful in curbing the disease progression in rice.